The COVID-19 Pandemic, Social Media Culture, and Public Education - Indah Chairun Nisa (Institut Agama Islam Negeri Palopo, 2022)
The purpose of this study is to examine the public education of COVID-19 through the use of social and cultural media. Additionally, this research examines how the media affects the community and the role of mass media communication in raising knowledge about COVID19 prevention and preventative measures. This study employs a qualitative method by adopting a virtual ethnographic approach, which refers to ethnographic research regarding the internet and social media conducted in online settings. The findings indicate that Indonesian social media culture can serve as a teacher by educating the public and stimulating interest in the latest research on COVID-19; by directing people to their websites and landing pages for information on the latest and most trusted COVID-19; by marketing innovative services such as health care social funding; and by posting case information, photos, and results (with permission) relating to COVID-19.